SOVEREIGNTY AND LEGAL PERSONALITY: A LESSON FROM EUROPEAN UNION'S EVOLUTION TO SUPRANATIONALISM - Muhammad Bahrul Ulum (Faculty of Law Universitas Lampung, 2022)
Sovereignty remains a crucial debate in international law. Simultaneously, regionalism offers a new pathway for which sovereignty is often contested whether it surrenders due to economic interests. This paper revisits the notion of state sovereignty in the light of economic globalization and enquires about legal personality in international relations. Overall, this paper emphasizes revisiting the concept of sovereignty and legal personality in this 21st century, which has evolved amidst the more globalized world due to international economic relations. The present study was based on historical and analytical methods as doctrinal research. The historical approach was adopted to study international treaties and agreements to know the historical background and evolution of international economic law institutions. Then, it exemplified the European Union's evolution that transcends the state boundaries, following the debate on the relevance of the state sovereignty after the Brexit case under the discussion of the waning of the state sovereignty. Finally, this discussion ended with the international legal personality owned by regional bodies, taking the EU and ASEAN as the comparison. At the outset, the EU was projected as the new governance structure that gradually disrupted the state concept under the Westphalian Peace 1648 due to its member states' desire to form the state-level structure. The European Union redefines the new model of sovereignty against the Westphalian model, which is incomparable to the ASEAN intergovernmental model and other regional bodies regarding sovereignty concerns and legal personality.